TERRORIST MINDSETS: destructive effects of victimisation and humiliation - Varvin, Sverre (Psyke & Logos, 2003)
Terrorist mindset is defined as a preparedness to hurt or kill innocent people for a »higher cause« (ideological, political or religious). It involves degrees of dehumanisation of other human beings and uses destructive and indiscriminate violence. Terrorist mindset may develop in individuals and groups in different contexts; in various terrorist groups (fundamentalist, political, vigilant etc), as state organised violence or in the context of organised military or paramilitary activity. Humiliation and traumatisation of groups or nations are seen as producing preconditions for the development of terrorist mindsets.